Abdurrahman Wahid’s Pribumisasi Islam, Democracy, and Religious Moderationin The Perspective of Habermas’ Communicative Action Theory - Hawasi, Hawasi (UIN Fatmawati Sukarno Bengkulu, 2023)
The aim of this study is to analyse Abdurrahman Wahid (Gus Dur)’s idea of Pribumisasi Islam in the prespective of Habermas’ Communicative Action theory. By using hermeneutic method the research tried to interprete Gus Dur’s idea of Islam and and its relationship with democracy. The texts choosen for this research were the writings of Gus Dur related idea of Pribumisasi Islam and democracy. From the texts were found that Pribumisasi Islam initiated by Gus Dur offers Islam in its ethical dimension as public religion which respects to democracy. It is line with what Habermas writes that religion should contribute its ethical value in plural public sphere. In this context, Gus Dur with his Pribumisasi Islam tries to presents the face of Islam which is in line withdemocracy. Gus Dur brings Islam as religion of humanity which respects to plurality of religions and cultures.Gus Dur believes that Pribumisasi Islam is the way of religious moderation in islam whichis compatible with democracy. In Pribumisasi Islam all elements of society, the global and the local, can involve participatorily in plublic sphere.